The Skill Development of Children of Immigrants - Marie C. Hull; Jonathan Norris (Institute of Labor Economics (IZA), 2018)
In this paper, we study the evolution of cognitive and noncognitive skills gaps for children of immigrants between kindergarten and 5th grade. We find some evidence that children of immigrants begin school with lower math scores than children of natives, but this gap disappears in later elementary school. For noncognitive skills, children of immigrants and children of natives score similarly in early elementary school, but a positive gap opens up in 3rd grade. We find that the growth in noncognitive skills is driven by disadvantaged (e.g., low-SES) immigrant students. We discuss potential explanations for the observed patterns of skill development as well as the implications of our results for the labor market prospects of children of immigrants.
Keywords: I21; J13; J15; 330; children of immigrants; cognitive and noncognitive skills; test score gap